Finding new friends and revisiting old ones – how plant lipid droplets connect with other subcellular structures. Issue 3 (5th August 2022) - Scholz, Patricia; Chapman, Kent D.; Mullen, Robert T.; Ischebeck, Till
Summary: The number of described contact sites between different subcellular compartments and structures in eukaryotic cells has increased dramatically in recent years and, as such, has substantially reinforced the well‐known premise that these kinds of connections are essential for overall cellular organization and the proper functioning of cellular metabolic and signaling pathways. Here, we discuss contact sites involving plant lipid droplets (LDs), including LD‐endoplasmic reticulum (ER) connections that mediate the biogenesis of new LDs at the ER, LD‐peroxisome connections, that facilitate the degradation of LD‐stored triacylglycerols (TAGs), and the more recently discovered LD‐plasma membrane connections, which involve at least three novel proteins, but have a yet unknown physiological function(s).